Sweden now 1979-I_4 - Testologen Ltd. (IMU-Testologen AB, 1983)
In the middle of the sixties Testologen AB, in cooperation with a group of advertisers, introduced a new way of investigation where data about the target groups, i.e. interests, consumer habits, possessions, buying intentions, and data about reading habits were collected in the same survey. At SSD there are now surveys available from the Sweden Now series covering the period 1972-1991.
In the 1977 survey the respondents had to indicate their reading habits concerning fifteen different daily papers, weekdays and weekends respectively. They also had to state their reading habits concerning nearly fifty papers from the weekly and monthly press. Other questions dealt with the household´s possession of a number of capital goods such as, car, camera, projector, washing machine, dishwasher, etc., and also if there were any dogs, cats, aquarium fishes or cagebirds in the household. A group of questions is dealing with buying habits and purchasing intentions for a number of products. A number of questions about personal interests are introduced by ´Human interests are different. How great is your interest for the following subjects and activities´. Subsequently the respondent is asked how interested he/she is in buying food, cooking, having guests, leisure time activities, etc. Furthermore the respondents had to indicate if they agreed or disagreed with a number of statements concerning life style. There is information about the respondent´s gender, marital status, age, income, occupation, education and housing, and also about the household´s size, age structure, and total income of household. A major part of Sweden Now 1979 is a replication of earlier surveys. A new addition for this survey is a group of questions dealing with the respondents influence on purchases at the place of work.

Purpose:

Collect broad information about interests, purchasing habits and media choices

Subset of Sweden Now 1979-I, covering the period 1978-11-29 to 1979-01-29.

In the middle of the sixties Testologen AB, in cooperation with a group of advertisers, introduced a new way of investigation where data about the target groups, i.e. interests, consumer habits, possessions, buying intentions, and data about reading habits were collected in the same survey. At SSD there are now surveys available from the Sweden Now series covering the period 1972-1991.
In the 1977 survey the respondents had to indicate their reading habits concerning fifteen different daily papers, weekdays and weekends respectively. They also had to state their reading habits concerning nearly fifty papers from the weekly and monthly press. Other questions dealt with the household´s possession of a number of capital goods such as, car, camera, projector, washing machine, dishwasher, etc., and also if there were any dogs, cats, aquarium fishes or cagebirds in the household. A group of questions is dealing with buying habits and purchasing intentions for a number of products. A number of questions about personal interests are introduced by ´Human interests are different. How great is your interest for the following subjects and activities´. Subsequently the respondent is asked how interested he/she is in buying food, cooking, having guests, leisure time activities, etc. Furthermore the respondents had to indicate if they agreed or disagreed with a number of statements concerning life style. There is information about the respondent´s gender, marital status, age, income, occupation, education and housing, and also about the household´s size, age structure, and total income of household. A major part of Sweden Now 1979 is a replication of earlier surveys. A new addition for this survey is a group of questions dealing with the respondents influence on purchases at the place of work.

Syfte:

Samla in en bred information om intressen, köpvanor och mediaval

Delmängd av ORVESTO 1979-I omfattande perioden 1978-11-29 till 1979-01-29.
ORVESTO 1979-I_4
Sverige nu 1979-I
Keywords: consumption; konsumtion; newspaper readership; tidnings läsekrets; periodicals readership; tidskrifts läsekrets; shopping; shopping; decision making; beslutsfattande; retail outlets; försäljningsställen; domestic appliances; hushållsapparat; consumer goods; konsumtionsvaror; attitudes; attityder; interest (cognitive processes); intresse (kognitiva processer); frequency; frekvens; Consumption and consumer behaviour; Konsumtion och konsumentbeteende; Media; Media; Public relations; Public relations; Social Sciences; Samhällsvetenskap; Media and Communication Studies; Medie- och kommunikationsvetenskap